2013
DOI: 10.1155/2013/602029
|View full text |Cite
|
Sign up to set email alerts
|

4-Hydroxyhexenal- and 4-Hydroxynonenal-Modified Proteins in Pterygia

Abstract: Oxidative stress has been suspected of contributing to the pathogenesis of pterygia. We evaluated the immunohistochemical localization of the markers of oxidative stress, that is, the proteins modified by 4-hydroxyhexenal (4-HHE) and 4-hydroxynonenal (4-HNE), which are reactive aldehydes derived from nonenzymatic oxidation of n-3 and n-6 polyunsaturated fatty acids, respectively. In the pterygial head, labeling of 4-HHE- and 4-HNE-modified proteins was prominent in the nuclei and cytosol of the epithelium. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…The ROS formed as a consequence of UV-B radiation have the potential to cause lipid peroxidation in cellular membranes, thus promoting the degeneration of polyunsaturated fatty acids (PUFAs) into various compounds, including the reactive aldehydes 4-hydroxyhexenal (4-HHE) and 4-hydroxynonenal (4-HNE). 51,52 These molecules have been found in increased levels throughout the pterygial specimens, including the head, where the corneal-migration occurs at the front of the pterygium, and the body, where active proliferation of subepithelial connective tissues occurs. 52 4-HHE and 4-HNE have the potential to modify proteins and affect their normal function by reacting with histidine, cysteine, and lysine residues.…”
Section: Causative Factors Uv Radiationmentioning
confidence: 99%
See 2 more Smart Citations
“…The ROS formed as a consequence of UV-B radiation have the potential to cause lipid peroxidation in cellular membranes, thus promoting the degeneration of polyunsaturated fatty acids (PUFAs) into various compounds, including the reactive aldehydes 4-hydroxyhexenal (4-HHE) and 4-hydroxynonenal (4-HNE). 51,52 These molecules have been found in increased levels throughout the pterygial specimens, including the head, where the corneal-migration occurs at the front of the pterygium, and the body, where active proliferation of subepithelial connective tissues occurs. 52 4-HHE and 4-HNE have the potential to modify proteins and affect their normal function by reacting with histidine, cysteine, and lysine residues.…”
Section: Causative Factors Uv Radiationmentioning
confidence: 99%
“…51,52 These molecules have been found in increased levels throughout the pterygial specimens, including the head, where the corneal-migration occurs at the front of the pterygium, and the body, where active proliferation of subepithelial connective tissues occurs. 52 4-HHE and 4-HNE have the potential to modify proteins and affect their normal function by reacting with histidine, cysteine, and lysine residues. 53 Such protein modifications have been found to be prominent in pterygium tissue, as opposed to normal conjunctiva.…”
Section: Causative Factors Uv Radiationmentioning
confidence: 99%
See 1 more Smart Citation
“…4-Hydroxynonenal has been previously reported to be associated with ocular surface diseases 9 10 11 12 . The novel evidence of this present study demonstrated that 4-HNE contributes to oxidative stress in corneal epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…Extensive research suggests that oxidative stress plays vital roles in the pathogenesis of many ocular diseases. Multiple clinical and experimental studies demonstrated that 4-Hydroxynonenal is associated with some ocular surface diseases, including granular corneal dystrophy, atopic keratoconjunctivitis, pterygium, and dry eye 9 10 11 12 , as well as cataract 13 , age related macular degeneration (AMD) 14 and diabetic retinopathy 15 , while the role and the underlying mechanism of 4-HNE in the eyes remain largely unknown. The aim of this present study was to focus on and investigate the association between 4-HNE and oxidative stress in the corneal epithelium and explore the underlying mechanistic.…”
mentioning
confidence: 99%